(untitled) (Journal of actual problems of jurisprudence, 2018)
In the analysis of the status and structure of ecological legislation matter in the EAEC countries should be sever two directions: the first – about the sources of law especially the lawmaking process and its outcomes in separated EAEC countries and the second – about trends in ecological legislation in the Union in whole. It is possible to say that trends of lawmaking development and ecological law structures’ formation differ in uniformity. Under state control in the sphere of ecology it is necessary to understand executive and administrative activities of relevant government authorities which aims to environmental efficient ensure and environmental protection. Key words: Eurasian Union, ecological lawmaking, unification, ecological situation.